ORNAMEN JEPARA SEBAGAI UNSUR HIAS KURSI MAKAN - Nilam APMN; Jati Widagdo (SULUH: Jurnal Seni Desain Budaya, 2019)
Dining chairs as complementary facilities need a comfortable and aesthetic design, in this case the Jepara ornament as the basic idea of creating a dining chair that emphasizes function and aesthetic value. The purpose of making this final project is to create a dining table with Jepara ornaments as a form idea to create creative and innovative dining chairs.The purpose of making the design is to create a dining table with Jepara ornaments as a form of idea to create creative and innovative dining chairs. The dining chair is a complementary facility for the house in the dining room The Jepara ornament is a stylization of the wuni fruit shape which has a characteristic with the fruit located between the leaves. The Jepara ornament as an ornamental element in the creation of a dining chair is a creative and innovative design. The main function of the dining chair is, as a means to eat and as a complement to the dining room